A New Amphiphilic Brønsted Acid as Catalyst for the Friedel–Crafts Reactions of Indoles in Water. Issue 1 (27th December 2018) - Cheng, Yuan; Ou, Xiongyu; Ma, Jimei; Sun, Linhao; Ma, Zhong‐Hua
Abstract : A new amphiphile1a featuring with two ‐NHSO2 C4 F9 sites is designed and synthesized as Brønsted diacid. The amphiphilicity arose from nano‐aggregations of hydrophobic fluorocarbon chains and extension of hydrophilic NH groups, confirmed by Tyndall effect and TEM. The acidity of1a rivals to concentrated H2 SO4, examined by the Hammett acidity function, 31 P NMR and conductance titration. Compound1a demonstrated excellent catalytic performance in the Friedel–Crafts alkylation of indoles in water. Reactive substrates, such as β‐monosubstituted vinyl ketones in 1, 4‐addition and aldehydes in condensation, were quantitatively converted, and the products were easily isolated by filtration or extraction in 85–96 % yields. Additionally, there was no observation of effect of the acidity weakening of1a on catalysis when poor‐reactive substrates were used, such as β, β‐disubstituted vinyl ketones in 1, 4‐addition and ketones in condensation. The two kinds of reactions were practised very smoothly. The formed nano‐aggregations and the strong acidity of1a were responsible for the highly efficient aqueous catalysis. Notably, 1a was recycled at least 3 times thanks to its amphiphilic structure. It was demonstrated the nano‐aggregations played a key role in the aqueous synthesis. Abstract : A designed Brønsted acid enables Friedel–Crafts alkylation of indoles in water, whose hydrophobic aggregations of fluorocarbon chains, along with phenyl ring, protected acid sites from bulk water and enriched the substrates. The amphiphilic structure has been proven crucial for the high catalytic efficiency.